Improvement of the Photosynthetic Characteristics and Yield of Wheat by Regulating the Proportion of Nitrogen Fertilizer Base and Topdressing - Yaoyuan Zhang; Haiqi Wang; Rongrong Wang; Fangfang He; Guiying Jiang; Jianwei Xu (Agronomy)
This study developed a nitrogen management framework that simultaneously addresses photosynthetic limitations and water scarcity challenges, providing a scalable solution for sustainable wheat production in arid farming systems. Focusing on Xinjiang’s arid region, we investigated how different ratios of basal to topdressed nitrogen fertilization affect photosynthetic mechanisms in drip-irrigated spring wheat. We implemented a split-plot design during the 2020–2021 growing seasons, using two wheat cultivars as main plots: strong-gluten Xinchun 37 (XC37) and medium-gluten Xinchun 6 (XC6). The subplots consisted of five N application treatments: N00: (no nitrogen application, control), N28 (base fertilizer 20%, top dressing 80%, and so on), N37 (3:7), N46 (4:6), and N55 (5:5). The vast majority of indicators performed best under N37 treatment. And LAI, RuBPC (ribulose-1,5-diphosphate ribulose carboxylase) activity, net photosynthetic rate (Pn), yield, and its composition were higher than the rest of the treatments by 0.21~31.75%, 6.94~25.21%, 7.42~40.78%, 0.86~25.44%, and 0.44~12.02%. And intercellular CO2, concentration (Ci) was lower than other treatments by 7.63~50.60%. Yield showed q highly significant positive correlation with Pn, Gs, Tr, ΦPSⅡ, and chlorophyll fluorescence parameters, but a negative correlation with Ci. Stepwise regression analysis showed that LAI, Pn, Ci, and RuBPC activity had a significant impact on yield and its compositions. In addition, all index performances of XC37 were better than XC6. Under drip irrigation in arid zones, allocating 30% basal + 70% topdressed N optimally enhances photosynthetic capacity and yield formation in spring wheat, offering a practical pathway for sustainable intensification in water-limited agroecosystems.